2009
DOI: 10.1007/s00277-009-0836-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of serum free light chains predict renal recovery

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…One study assayed serial samples from 17 myeloma patients and found that serum FLC concentrations fell more rapidly in response to treatment than did intact immunoglobulin G, and correlated closely with the level of bone marrow plasma cells and serum b2 microglobulin concentrations [13]. There are also some early data that in patients with acute kidney injury due to myeloma, reducing serum FLC concentration by utilizing chemotherapy accompanied by a high cut-off dialyzer may lead to improved renal recovery [14]. Additionally, myeloma patients in whom the myeloma protein is undetectable by IFE as a consequence of therapy, who also normalize the j/k FLC ratio, have improved overall survival compared to those that do not [15].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…One study assayed serial samples from 17 myeloma patients and found that serum FLC concentrations fell more rapidly in response to treatment than did intact immunoglobulin G, and correlated closely with the level of bone marrow plasma cells and serum b2 microglobulin concentrations [13]. There are also some early data that in patients with acute kidney injury due to myeloma, reducing serum FLC concentration by utilizing chemotherapy accompanied by a high cut-off dialyzer may lead to improved renal recovery [14]. Additionally, myeloma patients in whom the myeloma protein is undetectable by IFE as a consequence of therapy, who also normalize the j/k FLC ratio, have improved overall survival compared to those that do not [15].…”
Section: Clinical Applicationsmentioning
confidence: 99%